Peer Conformity Affects Smoking Behavior among Male Adolescents in a High School in Padang, Indonesia - Mahathir, Mahathir; Vitamaharanie, Prilya; Hermalinda, Hermalinda (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Peers contribute to the development of adolescents’ behavior during the transition period. Adolescents often justify their behavior with peers to confirm social norms of their surroundings. The increasing number of male adolescent smokers is raising public awareness to become acquainted with the cause of the behavior. Peer conformity is expected to be one of the vital variables to circulate smoking behavior. Purpose: This study aimed to determine the correlation between peer conformity and smoking behavior among male adolescents in a high school in Padang, Indonesia.Methods: A descriptive-analytical research design with a cross-sectional approach was used in this study. The samples were 154 male adolescents recruited by proportional random sampling. The data were collected using the questionnaires and analyzed using the Fisher exact test. Results: The results showed a significant correlation between peer conformity and smoking behavior among male adolescents (p=0.000). Peer conformity contributed to the development of smoking behavior among adolescents in this study.Conclusion: Peer conformity was evident to have a significant correlation with smoking behavior among male adolescents. Increasing assertiveness and life skill ability might be a necessity to adapt to negative behavior among adolescents.